Alih Kode dan Campur Kode dalam Bertutur Mahasiswa Jurusan Pendidikan Bahasa dan Sastra Indonesia Kampus UIN Jakarta - Anggraini, Dwi Puji; Ariana, Tanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The purpose of this study is to explain the types, factors that cause the occurrence, and the form of elemental division of code-switching and code-mixing events in students majoring in Indonesian Language and Literature Education at UIN Syarif Hidayatullah Jakarta campus. This research belongs to qualitative research by applying descriptive qualitative method. The discussion is presented in the form of narratives and tables of research results. The data sources are obtained from the utterances between students in the process of interaction or conversation produced by speakers containing elements of code switching and code mixing. The speech analyzed in this study includes words, phrases, or sentences of speech in the interaction between speakers. In the process of data collection, this research uses literature review techniques, observation (direct review), and field notes. After the analysis, it is found that students make utterances that contain elements of code switching and code mixing. The results of the study explained that students majoring in PBSI UIN Jakarta said utterances involving internal code switching from Indonesian to Sundanese and were influenced by speech partner factors. Meanwhile, the code mix that occurs in the students' speech is external code mix from Sundanese to English and mixed code mix, namely Indonesian with Sundanese and English. The factors causing the occurrence of code-mixing events are influenced by the speakers' habits and background factors. The form of insertion that occurs in the utterance is word insertion.